Lattice QCD studies on baryon interactions in the strangeness -2 sector with physical quark masses - Sasaki Kenji; Aoki Sinya; Doi Takumi; Gongyo Shinya; Hatsuda Tetsuo; Ikeda Yoichi; Inoue Takashi; Iritani Takumi; Ishii Noriyoshi; Miyamoto Takaya (EPJ Web of Conferences, 2018)
We investigate baryon-baryon (BB) interactions in the strangeness S = −2 sector via the coupled-channel HAL QCD method which enables us to extract the scattering observables from Nambu-Bethe-Salpeter (NBS) wave function on the lattice. The simulations are performed with (almost) physical quark masses (mπ = 146MeV) and a huge lattice volume of La = 8.1fm. We discuss the fate of H-dibaryon state through the ΛΛ and NΞ coupled-channel scatterings